2017
DOI: 10.1248/bpb.b17-00083
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing Effect of P2X7 Receptor Antagonist on Melanoma <i>in Vitro</i> and <i>in Vivo</i>

Abstract: Melanoma is highly malignant, and generally exhibits radioresistance, responding poorly to radiation therapy. We previously reported that activation of P2X7, P2Y6, and P2Y12 receptors is involved in the DNA damage response after γ-irradiation of human lung adenocarcinoma A549 cells. However, it is not clear whether these receptors are also involved in the case of melanoma cells, although P2X7 receptor is highly expressed in various cancers, including melanoma. Here, we show that P2X7 receptor antagonist enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…Considering the cell cycle arrest in irradiated cells, the cell proliferation could be decreased in irradiated cells. Cellular DNA damages are usually repaired in a few hours, 46,47) but in this study DNA damage response and repair factors were still not disappeared at 48 h after γ-irradiation. Previously, a phenomenon called senescencelike growth arrest (SLGA) was reported as a growth arrest reaction induced by radiation, 48) in which ATM and γH2AX were continuously activated.…”
Section: -23)contrasting
confidence: 56%
“…Considering the cell cycle arrest in irradiated cells, the cell proliferation could be decreased in irradiated cells. Cellular DNA damages are usually repaired in a few hours, 46,47) but in this study DNA damage response and repair factors were still not disappeared at 48 h after γ-irradiation. Previously, a phenomenon called senescencelike growth arrest (SLGA) was reported as a growth arrest reaction induced by radiation, 48) in which ATM and γH2AX were continuously activated.…”
Section: -23)contrasting
confidence: 56%
“…We previously reported that ATP is released from B16 melanoma cells after gamma irradiation and the release is mediated by P2X7 receptor and connexin 43. 5,6) We also showed that inhibition of P2X7 receptor had a radiosensitizing effect. 7) In the present work, we focused on adenosine, which is a metabolite of extracellular ATP, based on a recent report that adenosine is present at high concentrations around tumor tissue.…”
Section: Introductionmentioning
confidence: 83%
“…We have previously shown that P2X7 receptor-dependent ATP release occurs 1-10 min after γ-irradiation in B16 melanoma cells. 5,6) The released ATP promotes focus formation of the DNA damage repair marker γH2AX, with peaks at 30 min and 6 h after irradiation. We speculated that the peak at 30 min could be due to the rapid ATP release.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular nucleotides such as ATP (eATP), which are released into the extracellular space in response to cellular damage including ionizing radiation [124,128], act as autocrine or paracrine signaling molecules via activation of P2 receptors (P2Rs) on nearby cells [122][123][124][128][129][130][131][132][133][134]. In response to γ-irradiation, both human and murine cell lines have been shown to release ATP, thereby activating G protein-coupled P2Y [110,129,135] and ATP-gated ionotropic P2X receptors [126,136], which initiate purinergic signaling. Although no studies have yet investigated this bystander effect in IR-induced salivary gland dysfunction, we and others have reported on the expression of P2Y2, P2X7 and P2X4 receptors in In the past ten years, mounting evidence demonstrates that purinergic signaling can mediate the IR-induced bystander effect in adjacent, non-irradiated cells [110,[122][123][124][125][126][127][128].…”
Section: Bystander Effect: Potential Role For Purinergic Signalingmentioning
confidence: 99%
“…In response to γ-irradiation, both human and murine cell lines have been shown to release ATP, thereby activating G protein-coupled P2Y [110,129,135] and ATP-gated ionotropic P2X receptors [126,136], which initiate purinergic signaling. Although no studies have yet investigated this bystander effect in IR-induced salivary gland dysfunction, we and others have reported on the expression of P2Y2, P2X7 and P2X4 receptors in In the past ten years, mounting evidence demonstrates that purinergic signaling can mediate the IR-induced bystander effect in adjacent, non-irradiated cells [110,[122][123][124][125][126][127][128]. Extracellular nucleotides such as ATP (eATP), which are released into the extracellular space in response to cellular damage including ionizing radiation [124,128], act as autocrine or paracrine signaling molecules via activation of P2 receptors (P2Rs) on nearby cells [122][123][124][128][129][130][131][132][133][134].…”
Section: Bystander Effect: Potential Role For Purinergic Signalingmentioning
confidence: 99%